Η-Smarandache pseudo fuzzy ideal of a pseudo BH-algebra. (3rd July 2020) - Abbass, Hussain Hadi; Atshan, Falah Mahdi
Abstract: In this paper, the notion of a η -Smarandache pseudo fuzzy ideal of a pseudo BH- algebra is introduced. Some propositions and examples are investigated to study properties of this notion and to determine the relationships between it and a η -Smarandache pseudo ideal of a pseudo BH-algebra